Defense rights before the competition council in Algerian law - Boulares, Ahmed; Nakach, Hamza (Journal of Human Sciences, 2021)
In order to allow the Competition Council to perform its duties to the fullest.The Algerian legislature has given it a huge power similar to the oppressive power of a criminal justice. The most important authority is the one of the punishment which is traditionally from the jurisdiction of the criminal judge, but the legislator did not give it to him randomly, but rather gave the competition Council a package of restrictions most notably the commitment to the rights of the defense.